Rat nicotinic ACh receptor α7 and β2 subunits co-assemble to form functional heteromeric nicotinic receptor channels - Khiroug, Serguei S (Blackwell Science Inc, 2002)
Rat hippocampal interneurons express diverse subtypes of functional nicotinic acetylcholine receptors (nAChRs), including α7-containing receptors that have properties unlike those expected for homomeric α7 nAChRs. We previously reported a strong correlation between expression of the α7 and of the β2 subunits in individual neurons. To explore whether co-assembly of the α7 and β2 subunits might occur, these subunits were co-expressed in Xenopus oocytes and the functional properties of heterologously expressed nAChRs were characterized by two-electrode voltage clamp. Co-expression of the β2 subunit, both wild-type and mutant forms, with the α7 subunit significantly slowed the rate of nAChR desensitization and altered the pharmacological properties. Whereas ACh, carbachol and choline were full or near-full agonists for homomeric α7 receptor channels, both carbachol and choline were only partial agonists in oocytes expressing both α7 and β2 subunits. In addition the EC(50) values for all three agonists significantly increased when the β2 subunit was co-expressed with the α7 subunit. Co-expression with the β2 subunit did not result in any significant change in the current-voltage curve. Biochemical evidence for the co-assembly of the α7 and β2 subunits was obtained by co-immunoprecipitation of these subunits from transiently transfected human embryonic kidney (TSA201) cells. These data provide direct biophysical and molecular evidence that the nAChR α7 and β2 subunits co-assemble to form a functional heteromeric nAChR with functional and pharmacological properties different from those of homomeric α7 channels. This co-assembly may help to explain nAChR channel diversity in rat hippocampal interneurons, and perhaps in other areas of the nervous system.